ANALISIS PENGENDALIAN INTERNAL DALAM AKTIVITAS PEMBERIAN KREDIT DENGAN PENERAPAN KEARIFAN LOKAL “PADE GELAHANG” PADA SEKAA TUAK “ADA TUARA” DESA SEMBIRAN - I Kadek Ari Mahardika; Made Aristia Prayudi (Universitas Pendidikan Ganesha, 2022)
The present research aimed to find out how the application of local wisdom “Pade Gelahang” as an internal control system in giving credit to SekaaTuak “Ada Tuara”. This study used qualitative research. The data used in this research were primary data and secondary data. The result of this study showed that; the internal control system in Sekaa Tuak “Ada Tuara” based on the awig-awig Sekaa Tuak along with applying local wisdom “Pade Gelahang”. The “ketekel” sanction was the application of the local wisdom “Pade Gelahang” which namely the imposition of a 50% fine of the interest for sekaa tuak members not pay credit. The application of local wisdom